Teaching Strategies in Speaking Class of Second Semester Students at UIN Raden Mas Said Surakarta - Firdausi, Zakiya Nauroh; Budiharso, Teguh; Arini, Yusti; Sabariyanto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research objective is to analyze the teaching speaking strategies applied to second semester students in English Language Education study program at UIN Raden Mas Said Surakarta. In this study, the researcher used qualitative approach with ethnography design. The researcher collected the data by conducting observation, interview, and documentation. The participants are second semester students and teacher in speaking class in English Education Program. For the technique of analyzing data, the researcher used pre-fieldwork analysis, data collection, interative analysis, identifying patterns and themes, theoretical frameworks, coding, and report writing. The result from this study is teacher use the presentation, situational play/ simulation, and Q&A as the teaching strategies.